KANDUNGAN C-ORGANIK DAN N-TOTAL PADA SERESAH DAN TANAH PADA 3 TIPE FISIOGNOMI (Studi Kasus di Wanagama I, Gunung Kidul, DIY) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Abstract Wanagama I is considered a criticalarea having solum less than 10/20 cm with soil order of Lithosol (Entisol). The area has been developed since 1966 by planting with vegetation pioneers. The objective of this research was to determine the biomass weight of forest floor and the content of C and N in the forest floor and soil under three physiognomy types. Three physiognomy types are physiognomy I dominated by Melaleucacajuput